Analisis Implementasi Etika Kerja Islam, Ekonomi Hijau dan Kesejahteraan dalam Prespektif Ekonomi Islam - Ely Fitri Wahyuni; Syamsul Hilal; Madnasir Madnasir (Jurnal Ilmiah Ekonomi Islam, 2022)
Indonesia is the second richest country in the world for terrestrial and marine biodiversity. Non-renewable natural resources worsen environmental resources because of human behavior that is not environmentally friendly. Meanwhile, threats due to climate change and global warming are increasingly reducing the sustainability of the earth in meeting the needs and welfare of mankind. The green economy is a model of the concept of economic development that no longer relies on development based on excessive exploitation of natural resources and the environment. On the other hand, Welfare is something that everyone wants to achieve, both individual welfare and family welfare. One of the villages that has natural wealth is Labuhan Baru Village, which is one of the Way Serdang District Villages which is located directly adjacent to South Sumatra. The area of Labuhan Baru Village is 1,240 KM. The Labuhan Baru community based on the village profile in 2020, the daily livelihood of the residents is the majority of rubber farmers. Based on observations made by researchers, it is interesting that not all plantation sectors have good potential in the green economy such as secondary crops, rice and so on. Rubber trees have good potential for the concept of a green economy, namely the existence of a sustainable economy that is environmentally friendly. Seeing from that, the majority of the religion of Labuhan Baru Village is Muslim where Muslims themselves uphold ethics. This is a question of researchers how the practices carried out by the people of Labuhan Baru Village on Islamic work ethics, green economy and welfare in the perspective of Islamic economics. This study aims to analyze how the implementation of the Labuhan Baru Village community in implementing Islamic work ethics, green economy and welfare in the perspective of Islamic economics. The type of data used is primary data obtained directly by the rubber farming community of Labuhan Baru Village. The results of this study indicate the implementation of Islamic work ethics, green economy and welfare of rubber farmers in Labuhan Baru Village, Way Serdang District, Mesuji Regency in accordance with the perspective of Islamic economics. The implementation carried out by rubber farmers in Labuhan Village is in accordance with Islamic teachings that have been taught. But unfortunately the rubber farmer community awareness of formal education is still somewhat less, they are more inclined towards non-formal education, namely Islamic boarding schools, seeing from the statements of the rubber farming community in Labuhan Baru Village, this is reinforced by data on education graduates obtained from the Labuhan Baru Village profile in 2020 from the population of 1759 for undergraduate graduates is 15 and for masters as many as 1. According to researchers this is one of the factors in implementing Islamic work ethics, green economy and welfare are still using the traditional way.